Sunlight and lifestyle: linking prenatal light conditions and personality development in a wild bird. (November 2022) - Ruiz-Raya, Francisco; Velando, Alberto
Abstract : Even though personality is a major determinant of individual survival, the development of animal personality traits is still poorly understood. Beyond an individual's genetic background, personality may be shaped by the conditions experienced during embryonic development. Light is a salient and variable ecological factor that can affect organismal physiology, establish brain asymmetries and ultimately modulate postnatal phenotypes across multiple taxa. Exposure to light is known to vary among avian embryos due to changes in parental incubatory constancy, but whether differences in the prenatal light environment can influence offspring personality development has rarely been explored. Here, we investigated whether the prenatal light environment shapes a key dimension of animal personality, the shy–bold axis, in hatchlings of a semiprecocial seabird, the yellow-legged gull, Larus michahellis . In gulls, the prenatal light environment may be especially important for last-laid eggs, as parental attendance during late incubation is more variable for last-laid than for senior eggs. We manipulated the levels of embryonic exposure to light (within the natural range previously documented in the wild) during the last stages of egg incubation and assessed differences in boldness in newly hatched junior chicks. We then used structural equation modelling to explore whether the effect of prenatal light exposure on the shy–bold axis is linked to the establishment of brain asymmetries (lateralization) and/or changes in plasma corticosterone levels. Prenatal light exposure promoted bolder phenotypes in gull chicks, which may improve their individual performance when competing for parental resources. Prenatal light also promoted the lateralization of the begging behaviour in newly hatched chicks, which was negatively associated with boldness. Finally, light induced changes in glucocorticoid levels, but these changes did not impact chicks' personality. Our findings unambiguously confirm that the prenatal light environment strongly affects the development of shy–bold phenotypes in gull hatchlings through a complex multipath mechanism. Highlights: Can the prenatal environment shape animal personality? Last-hatched gull eggs are highly exposed to sunlight during late incubation. We explored whether prenatal exposure to light shapes boldness in hatchlings. Prenatal light promoted bold phenotypes and brain lateralization in gull chicks. These adjustments might improve chick performance under competitive disadvantage.